2008
DOI: 10.1002/dvdy.21559
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and adiponectin receptor genes are coexpressed during zebrafish embryogenesis and regulated by food deprivation

Abstract: Adiponectin is an adipocytokine that plays important roles in glucose and lipid homeostasis. Adiponectin binds to two types of transmembrane receptors: Adiponectin receptor (AdipoR) type 1 and 2. We isolated and characterized the two adiponectin genes (adiponectin A and B) and the three adiponectin receptors in zebrafish. In adult, adiponectin A is only detected in the kidney while adiponectin B mRNAs are widely expressed and are detected in the liver, adipose tissue, muscle, and brain. The receptors are found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 39 publications
2
67
0
Order By: Relevance
“…A reduction in the expression of adiponectin in adipose tissue was found after a fasting period, while the expression of adipoR1 increased in the muscle of mice (Bertile and Raclot, 2004;Tsuchida et al, 2004) and in the liver of zebra fish (Nishio et al, 2008).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…A reduction in the expression of adiponectin in adipose tissue was found after a fasting period, while the expression of adipoR1 increased in the muscle of mice (Bertile and Raclot, 2004;Tsuchida et al, 2004) and in the liver of zebra fish (Nishio et al, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…Nevertheless, there is little information available about adipokines in lower vertebrates such as fish. Although the presence of leptin and tumour necrosis factor  (TNF) has been described in various fish species (Kling et al, 2009;SaeraVila et al, 2007), adiponectin has been identified in zebra fish (Nishio et al, 2008), and only very recently in rainbow trout (Kondo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, adipose tissue in lower exothermic animals is usually small because the liver performs the major lipid-storing function. Interestingly, in these animals, the liver secretes many of the mammalian orthologs of the adipokines, such as adiponectin and leptin (Huising et al, 2006;Nishio et al, 2008;Pfundt et al, 2009).…”
Section: Box 2 Strategies For Tag Synthesismentioning
confidence: 99%
“…As predicted, inversion of phtf1 GtN/+ or Felix-ina GtN/+ with Cre or Flp recombinase did not activate mCherry expression because the fluorescent protein is out of frame. Highlighting the increased sensitivity of LM-PCR compared with fluorescent detection, mCherry expression was not detected in adipor2 GtN embryos following inversion even though it was fused in frame, which was likely due to the low level of expression at this locus (12). We analyzed the effects of intronic insertions on host gene mRNA expression by quantitative RT-PCR (qRT-PCR) (primers listed in Table S1).…”
Section: Resultsmentioning
confidence: 99%